HUBUNGAN DUKUNGAN KELUARGA DENGAN KETAATAN MINUM OBAT PADA PASIEN DIABETES MELLITUS - Maylinda Wahyuning Putri; Habid Al Hasbi; Luluk Lusiati Cahyarini (Jurnal Cakrawala Keperawatan, 2025)
Background: Diabetes melitus is a chronic disease that occurs in a person due to inscreased blood sugar levels. This disease is characterized by chronic metabolic disorders characterized by hyperglycemia, in people with diabetes melitus, the body’s ability to react to insulin can decrease, or the pancreas can stop producing insulin. Diabetes melitus occurs when the body cannot utilize some foods due to lack of insulin production. Decreased pancreas and reduced secretion are caused by inscreasing age. The development of this disease toward complication is related to high blood sugar levels in sufferers which affect the performance of other organs of the body Purpose: The purpose of the study was to determine the relationship between family support and medication adherence in patients with diabetes mellitus at Waras Wiris Hospital Methods: This study used an analytical approach, with a cross sectional design in poly patients at Waras Wiris Hospital with sampling using purposive sampling of 36 respondents after being calculated with the slovin formula. The research instrument was in the form of a questionnaire on Family Support and Medication Compliance in Diabetes Mellitus Patients which was given to respondents to collect research data Results: The results of bivariate analysis proved that there was a relationship between family support and medication adherence in patients with diabetes mellitus obtained a significance value (p value) of 0.002 < ? (0.05) Conclusion: There was a relationship between family support and adherence to taking medication in patients with diabetes mellitus at Waras Wiris Hospital.